'Harder' soft governance in the European Energy Union. Issue 6 (1st November 2020) - Knodt, Michèle; Ringel, Marc; Müller, Rainer
ABSTRACT: In 2016, the Commission proposed an ambitious governance strategy in order to further the transformation of the European energy system towards the Unions' 2030 climate and energy targets. Therein the EU adopted the Regulation on the Governance of the Energy Union in 2018 to harden its otherwise soft governance. This contribution firstly aims at characterizing the 'hardness' of this soft governance. The analyses showed the introduction of harder elements to soft governance to at least a certain extend. Secondly, it explains the degree of hardness from actor-centred institutionalism perspective by analysing the trilogue of the co-legislators and the Commission. The analysis shows a successful entrepreneurial role of the Commission in those questions where it was backed by the European. The Parliament performed strongly due to powerful support of its joint committee, experienced negotiators and a wide majority voting in the plenum. In contrary, the Council showed a divided opinion in many points and was confronted with a weak presidency during the dialogue. As a result, harder elements were introduced in questions, where Commission and Parliament argued along the same lines and could even go beyond the Commissions' proposal, where Parliament and Council found points of common interest.